Socio-Economic Impacts of Energy Poverty on Households in Ikorodu Communities, Lagos State, Nigeria - Akande, Alex Adekoya; Akindele, Aarinola Abosede; Owolabi, Abayomi Justine (Journal of Sustainability and Environmental Management, 2024)
The study investigated the Ikorodu community's energy poverty status by adopting the Multidimensional Energy Poverty Index to assess each sub-community, as it centers on energy poverty. The study used both quantitative and qualitative assessments of data obtained from primary and secondary sources. The primary data was sourced from a questionnaire administered to households while secondary data was sourced mostly from the National Bureau of Statistics’ Nigeria Living Standard Survey (NLSS) dataset. Additional secondary data was obtained from the Lagos State socio-economic data survey which included the Ikorodu subset. The result showed that about half (42%) of the community was energy-poor while more than half (58%) were energy-non-poor. The study revealed energy poverty has a huge impact on the economic development of the studied communities, as there was a positive and significant correlation between energy poverty and educational, health, and economic activities. More specifically, energy poverty reduces social inclusion, diminishes the education level of the residents of the communities, lessens the quality of life and healthcare, and discourages business activities and the establishment of new businesses in the area. Given these findings, the study emphasizes the need for government intervention and public awareness to increase access to electricity through renewable energy sources. Additionally, it recommends promoting- clean and cost-effective energy alternatives to address the pressing issue of energy poverty within the community.